Correlation and thermodynamic analysis of solubility of diphenhydramine hydrochloride in pure and binary solvents. (February 2016) - Du, Shichao; Wang, Yan; Li, Jianyu; Wu, Songgu; Dun, Weiqiang; Song, Xiaopeng; Wang, Jingkang; Gong, Junbo
Graphical abstract: Highlights: The solubility of diphenhydramine hydrochloride in four pure and two binary solvents were experimentally determined. The experimental solubility of diphenhydramine hydrochloride were correlated by three models. The activity coefficients as well as thermodynamic properties of mixing were obtained and discussed. Abstract: The solubility of diphenhydramine hydrochloride (DH) in four pure solvents (methanol, ethanol, acetone and ethyl acetate) and two binary solvents (ethanol + ethyl acetate) and (ethanol + acetone) was determined at temperatures from (278.15 to 323.15) K. The experimental solubility of DH is well correlated by the modified Apelblat equation, the CNIBS/R-K equation and the hybrid model, respectively. All the measured solubility of DH shows temperature dependence. In binary mixtures, the solubility curve displays a maximum with the solvent composition changing, particularly, the maximum point increases with temperature. Moreover, the activity coefficients as well as thermodynamic properties of mixing were obtained and discussed.